Leadership Skills Configuration and Policy Implementation in Public Universities in Rivers State, Nigeria - Anietie, Richard (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
This study investigated leadership skill configuration and policy implementation in public universities in Rivers State. The study is intended to address issues on conceptual, technical and human relations leadership skills configuration of staff on leadership positions in public universities in Rivers state. It adopted a correlational research design using a population of 403 administrators in the 3 public universities in Rivers State. A sample size of 314 which was randomly selected was used in the conduct of the study. The study employed the use of a questionnaire which was self-designed and code named “Leadership Skill Configuration for Education Policy Implementation Questionnaire (LSCEPIQ)”. The instrument was validated by experts and its reliability was ascertained using Pearson Product Moment Correlation Coefficient 0.05 level of significance. The instrument after distribution has obtained a 100% retrieval. This was made possible because of the use of trained research assistants. The study used mean score and standard deviation statistical tools in its data analysis. The findings of the study revealed that conceptual, technical and human relations leadership skills configuration enhances greatly the process of policy implementation in public universities in Rivers State. Thus, the study recommended that, the university administrators at all levels to ensure the configuration of the conceptual, technical and human relations leadership skills of all their staff holding leadership positions to enhance better drive in policy implementation in public universities in Rivers state.